Application of the Betty Neuman Systems Model in Nursing Care of a Breast Cancer Patient: A Case Study - Atefeh Falakdami; Hossein Rafiei; Ali Razaghpoor (Journal of Social Behavior and Community Health, 2025)
Background: Nursing theories provide structured frameworks that guide practice and enhance care quality. The Betty Neuman Systems Model, widely utilized in the care of patients with chronic diseases, adopts a holistic approach by addressing various dimensions of a patient's health. Therefore, this study aims to apply the model in the nursing care of a patient with breast cancer. Methods: This case study, conducted in Iran in 2021, involved a 47-year-old breast cancer patient selected through purposive sampling. Data were collected via interviews, medical records, and physical examinations. Using the Betty Neuman Systems Model, the interactions among five key variables—physiological, psychological sociocultural, developmental, and spiritual—were assessed, and intra-, inter-, and extra-personal stressors, along with the patient's reactions, were identified. This, in turn, informed the formulation of nursing diagnoses and the development of a comprehensive care plan, which included goals, targeted interventions across three levels of prevention, and outcomes. Results: Analysis of the five variables and stressors resulted in 13 nursing diagnoses, including 8 actual and 5 risk diagnoses. The model's evaluation of the nursing care plan indicated positive outcomes for the patient. Conclusion: This study demonstrated the practical application of the Betty Neuman Systems Model in developing a personalized nursing care plan for a breast cancer patient. The findings highlight the model utility in addressing patients' holistic needs and provide practical insights for oncology nursing practice.